2013
DOI: 10.1371/journal.pone.0072264
|View full text |Cite
|
Sign up to set email alerts
|

The MicroRNAome of Pregnancy: Deciphering miRNA Networks at the Maternal-Fetal Interface

Abstract: MicroRNAs (miRNAs) post-transcriptionally regulate a vast network of genes by inhibiting mRNA translation. Aberrant miRNA expression profiles have been implicated in pathologies and physiological processes including pregnancy and angiogenesis. Using our established model of implantation failure and spontaneous fetal loss in pigs (Sus scrofa), 236 miRNAs were profiled and compared between 1) non-pregnant and pregnant endometrium, 2) maternal and fetal tissues, and 3) viable and growth-arrested conceptus attachm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 39 publications
3
47
0
Order By: Relevance
“…130 Additionally, our previous work identified endometrial dysregulation of several miRNAs including miR-10a, 49 133 and in our study profiling miRNAs at the porcine maternal-fetal interface, we identify regulation of blood vessel development/angiogenesis as being the third most important functional cluster increased in endometrium from pregnant pigs versus non-pregnant pigs. 49 Taken together, miRNA regulation of angiogenesis participates in both pathological and physiological angiogenesis, and offers a novel therapeutic avenue to explore. Let-7a and miR-320 72,73 Uterine miRNAs…”
Section: Microrna Regulation Of Angiogenesissupporting
confidence: 60%
See 3 more Smart Citations
“…130 Additionally, our previous work identified endometrial dysregulation of several miRNAs including miR-10a, 49 133 and in our study profiling miRNAs at the porcine maternal-fetal interface, we identify regulation of blood vessel development/angiogenesis as being the third most important functional cluster increased in endometrium from pregnant pigs versus non-pregnant pigs. 49 Taken together, miRNA regulation of angiogenesis participates in both pathological and physiological angiogenesis, and offers a novel therapeutic avenue to explore. Let-7a and miR-320 72,73 Uterine miRNAs…”
Section: Microrna Regulation Of Angiogenesissupporting
confidence: 60%
“…miRNAs have been implicated in endometrial receptivity, [34][35][36] implantation, 37-42 labor [43][44][45][46][47] and even spontaneous fetal loss in the pig. 48,49 In the uterus, most of the physiological changes occurring over the estrous/menstrual cycle and during pregnancy are driven by the ovarian hormones. In other organs and tissues, research has shown that there are many opportunities to regulate miRNAs; their transcription, processing, RNA editing, function and intracellular localization can all be modified, and thus affect miRNA binding of mRNAs (reviewed in.…”
Section: Microrna Regulation In the Uterusmentioning
confidence: 99%
See 2 more Smart Citations
“…Of such miRNAs that are silenced during fetal development, low abundance of miR-29 was reported in skin across several species. 7,75,76 In humans, hsa-miR-29a and hsa-miR-29b-1 (chromosome 7) and hsa-miR-29b-2 and hsa-miR-29c (chromosome 1) are highly conserved members of the miR-29 family that share the sequence homology at the seed region (nts 2-7) that decides the fate of coding genes. PTGS of multiple ECM proteins by the miR-29a-c family is one notable example of a single miRNA family regulating multiple ECM proteins such as different collagen isoforms, laminin 1, fibrilin 1, elastin, matrix metalloproteinase 2, hyaluronic acid, chondroitin sulfate, and integrin 1.…”
Section: Mirna and Regenerative Medicinementioning
confidence: 99%